2012
DOI: 10.5140/jass.2012.29.4.337
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Topside Additional Layer of Martian Ionosphere Using MARSIS/Mars Express Data

Abstract: In this study, the transient second or third layer on the topside of the Martian ionosphere were investigated with the most recently released Mars advanced radar for subsurface and ionospheric sounding/Mars Express data obtained from January 2010 to September 2011 to study the correlation between these topside additional layers and surface magnetic fields, solar zenith angle and solar activities. When examining the zones where the topside layer appeared, the occurrence rate of the topside layer was low at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The initial results reported by Kopf et al [] noted that these layers appeared all over the planet, including in the significantly less magnetized northern hemisphere. More recently it was demonstrated that the layer was almost exclusively present away from the main magnetism regions in the Southern Hemisphere, and especially common in the low‐magnetism regions [ Kim et al , ], a finding backed up by this study, which found the bulk of these layer detections to be in the Northern Hemisphere or near the equator, with less than a handful anywhere near the strong southern crustal field regions. This finding combined with those by Harada et al [] makes it possible that these are magnetized plasma parcels downstream from a more subsolar reconnection point.…”
Section: Possible Explanationssupporting
confidence: 64%
See 2 more Smart Citations
“…The initial results reported by Kopf et al [] noted that these layers appeared all over the planet, including in the significantly less magnetized northern hemisphere. More recently it was demonstrated that the layer was almost exclusively present away from the main magnetism regions in the Southern Hemisphere, and especially common in the low‐magnetism regions [ Kim et al , ], a finding backed up by this study, which found the bulk of these layer detections to be in the Northern Hemisphere or near the equator, with less than a handful anywhere near the strong southern crustal field regions. This finding combined with those by Harada et al [] makes it possible that these are magnetized plasma parcels downstream from a more subsolar reconnection point.…”
Section: Possible Explanationssupporting
confidence: 64%
“…This magnetism has been mapped all across the surface of the planet [ Connerney et al , ], and various spherical harmonic models have been devised to compute its components and strengths [e.g., Cain et al , ; Arkani‐Hamed , ]. Although Kopf et al [] found no direct correlation between the crustal fields and the detection of the second layer, a result supported by a significantly larger study [ Kim et al , ], the limited time range and indirect nature of that early study left room for the possibility of a connection on a broader scale.…”
Section: Features Of the Second Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Kopf et al () have discovered the existence of transient topside layers above the main ionospheric peak, at typical altitudes 180–240 km on the dayside, with an occurrence rate decreasing when going from the subsolar region to the terminator (from 60% to 5% of observation time). The topside layers are found mostly in regions of low crustal magnetic field strength (e.g., Kim et al, ; Kopf et al, ). It is not known whether topside layers exist in regions of stronger crustal fields, because the presence of electron cyclotron harmonics in the ionograms can hinder the visibility of the ionospheric traces at low frequency, including any potential topside layer.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the inversion process is not unambiguous, and a unique solution is found by assuming a predefined electron density profile shape in the return signal gap region (Němec, Morgan, Gurnett, ). The electron densities are generally assumed to monotonically increase with decreasing altitude down to the altitude of the peak; that is, any density voids in the altitude profile/transient layers (Kim et al, ; Kopf et al, ; Withers, Fillingim, et al, ) cannot be evaluated.…”
Section: Data Setmentioning
confidence: 99%